Supplementing artemisinin positively influences growth, antioxidant capacity, immune response, gut health and disease resistance against Vibrio parahaemolyticus in Litopenaeus vannamei fed cottonseed protein concentrate meal diets. Issue 131 (December 2022) - Liu, Hongyu; Chen, Guofeng; Li, Lixian; Lin, Zhixuan; Tan, Beiping; Dong, Xiaohui; Yang, Qihui; Chi, Shuyan; Zhang, Shuang; Zhou, Xiaoqiu
Abstract: Artemisinin (ART) is a kind of Chinese herbal medicine worth exploring, which obtains various physiological activities. In order to study the prebiotic effect of ART on Litopenaeus vannamei fed cottonseed protein concentrate meal diets, six groups of isonitrogenous and isolipid diets were prepared (including the fish meal control group, FM; cottonseed protein concentrate replacing 30% fishmeal protein and supplementing ART groups: ART0, ART0.3, ART0.6, ART0.9, and ART1.2). The feeding trials was lasted for 56 days. The results showed that the final body weight, weight gain and specific growth rate of the ART0.6 group were the highest, yet the feed coefficient rate of the ART0.6 group was the lowest significantly ( P < 0.05). There was no significant difference in survival rate among treatments ( P > 0.05). In serum, the content of malondialdehyde in ART0 group was the highest ( P < 0.05); the activities of superoxide dismutase, catalase, phenol oxidase and lysozyme increased firstly and then decreased among the ARTs groups ( P < 0.05). The activities of intestinal digestive enzymes (including the trypsin, lipase and amylase) showed an upward trend among the ARTs groups ( P < 0.05). The histological sections showed that the intestinal muscle thickness, fold height and fold width in the FM group were significantly better than those in the ART0 group; while the mentioned above morphological indexes in the ART0 group were significantly lowest among the ARTs groups ( P < 0.05). Sequencing of intestinal microbiota suggested that the microbial richness indexes firstly increased and then decreased ( P < 0.05); the bacterial community structure of each treatment group was almost close; the relative abundance of pathogenic bacteria decreased significantly ( P < 0.05), such as the Proteobacteria and Cyanobacteria at phylum level, besides the Vibrio and Candidatus Bacilloplasma at genus level. In intestinal tissue, the relative expression levels of TOLL1, TRAF6 and Pehaeidih3 showed up-regulated trends, while the expression of Crustin and LZM firstly up-regulated and then down-regulated ( P < 0.05). The challenge experiment suggested that the cumulative mortality of FM group was significantly lower than that of ART0 group; besides the cumulative mortality firstly increased and then decreased between the ARTs groups ( P < 0.05). In conclusion, the dietary supplementation of ART can improve the growth, antioxidant capacity, immune response, gut health and disease resistance of the shrimp. To be considered as a dietary immune enhancer, the recommended supplementation level of ART in shrimp's cottonseed protein concentrate meal diets is 0.43%. Highlights: Artemisinin (ART) is a kind of Chinese herbal medicine worth exploring, which obtains various physiological activities. Based on the growth investigation, the recommended supplementary level of ART is 0.43%. ART supplementation improved growth, serum antioxidant and immunity, digestive capacity, intestine and hepatopancreas morphology, intestinal immune-related gene expression, and disease resistance against Vibrio parahaemolyticus in Pacific white shrimp fed with cottonseed protein concentrate meal diets. The microbial sequencing also excavated the beneficial effect of ART supplementation on shrimp intestinal health by reducing the abundance of opportunistic pathogens (Proteobacteria and Cyanobacteria at phylum level; Vibrio and Candidatus Bacilloplasma at genus level). ART can be considered as a potentially dietary immune enhancer to fortify shrimp fed with reducing-fishmeal diets, providing reference of dietary immunomodulating enhancer for shrimp.